Different molecular characteristics and antimicrobial resistance profiles of Clostridium difficile in the Asia-Pacific region. Issue 1 (1st January 2019) - Luo, Yun; Cheong, Elaine; Bian, Qiao; Collins, Deirdre A.; Ye, Julian; Shin, Jeong Hwan; Yam, Wing Cheong; Takata, Tohru; Song, Xiaojun; Wang, Xianjun; Kamboj, Mini; Gottlieb, Thomas; et al.
ABSTRACT: Molecular epidemiology of Clostridium difficile infection (CDI) has been extensively studied in North America and Europe; however, limited data on CDI are available in the Asia-Pacific region. A multicentre retrospective study was conducted in this region. C. difficile isolates were subjected to multilocus sequence typing (ST) and antimicrobial susceptibility testing. Totally, 394 isolates were collected from Hangzhou, Hong Kong, China; Busan, South Korea; Fukuoka, Japan; Singapore; Perth, Sydney, Australia; New York, the United States. C. difficile isolates included 337 toxin A-positive/B-positive/binary toxin-negative (A + B + CDT - ), 48 A - B + CDT -, and nine A + B + CDT + . Distribution of dominant STs varied geographically with ST17 in Fukuoka (18.6%), Busan (56.0%), ST2 in Sydney (20.4%), Perth (25.8%). The antimicrobial resistance patterns were significantly different among the eight sites ( χ 2 = 325.64, p < 0.001). Five major clonal complexes correlated with unique antimicrobial resistances. Healthcare-associated (HA) CDI was mainly from older patients with more frequent antimicrobial use and higher A - B + positive rates. Higher resistance to gatifloxacin, tetracycline, and erythromycin were observed in HA-CDI patients ( χ 2 = 4.76-7.89, p = 0.005-0.029). In conclusion, multiple C. difficile genotypes with varied antimicrobial resistance patterns have been circulating in the Asia-Pacific region. A - B + isolates from older patients with prior antimicrobial use were correlated with HA-CDI.